Preguntas y frases para una nieta americana - de Hinojosa, Alana (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
“Preguntas y frases” is an imagined letter from my grandmother. It is composed of Spanish words and phrases (including missing accents and misspellings) as my grandmother, Esther, wrote them in 1983 in a series of letters she sent to my mother while my mother was living abroad in Ecuador. In those letters, Esther spoken plainly with her daughter—principally, by questioning her decision to leave the United States and asking that my mother back home to Calexico, California.Many years after my grandmother’s death, my mother found these letters tucked away in the house attic. When my mother shared these letters with me, it was startling for me to see and hear so clearly my grandmother’s voice and way of speaking after so many years since her passing. In response, I wrote “Preguntas y frases para una nieta americana.” The title is inspired by Teresa Palomo Acosta’s poem “Preguntas y frases para una bisabuela española” in which Acosta reflects on her Spanish heritage by writing a letter to her great Spanish grandmother. In contrast, “Preguntas y frases para una nieta americana” reflects on American assimilation and what is lost, protected, and honored across three generations of Mexican American women. The letter is my imagination of what my grandmother would say to me today if she were to write me—and speak plainly—as she had with my mother all those years ago.